Education transformation: strategies and challenges in implementing educational technology - Purnawanto, Ahmad Teguh; Purwaningsih, Sri; Sutama, Sutama; Sutopo, Anam; Murtiyasa, Budi (Universitas Ahmad Dahlan, 2023)
The integration of innovation and technology into educational settings has emerged as a promising avenue for reshaping learning and teaching methodologies. However, this transformative process is not devoid of challenges, necessitating a comprehensive understanding to fully exploit its potential. This article aims to delineate best practices for implementing innovation and technology in elementary education environments. Employing a qualitative descriptive methodology, the research conducts semi-structured interviews with Information Technology (IT) learning support teachers in elementary schools. Through reflective thematic analysis, two primary perspectives emerge from the participants' experiences. Firstly, participants underscore the potential of IT-based learning innovation in elementary schools. They emphasize that leveraging innovative educational technology can foster a more engaging and adaptive learning environment, aligning with the evolving demands of the digital era. Secondly, the study identifies various challenges and corresponding opportunities associated with IT-based learning innovation. These complexities underscore the need for tailored adaptation efforts to effectively implement innovative teaching approaches aligned with student needs. The findings suggest that addressing these challenges can enable schools to capitalize on the full potential of innovation and technology, thereby creating dynamic, inclusive learning environments responsive to future demands. This research contributes to the literature by providing insights into the practical implications of integrating innovation and technology in elementary education, offering guidance for educators and policymakers seeking to navigate and maximize the benefits of educational innovation.